POETRY APPRECIATION TEACHING MATERIAL DESIGN BASED ON CONTEXTUAL APPROACH - Hidayat, Arip; Muliastuti, Liliana; Dewanti, Ratna (University of Kuningan, 2022)
Teaching materials are needed as learning resources that should be adapted based on students’ conditions. The contextual approach is a suitable approach to meet the needs of students in learning in order the improvement of learning outcomes can be carried out. Appreciation of poetry as a course in the department of Indonesian language and literature education requires development to obtain learning outcomes and adjustments on student conditions and the times. The development of such a theory has led this research to develop the design of teaching materials as an intellectual framework and the basis of reference from teaching materials for poetry appreciation. This research uses a qualitative approach and descriptive methods to define needs from the point of view of students, lecturers, and experts in the field of poetry appreciation. The results of the study showed the need in terms of content and strengthening the theory. In the elements of the book, the graphics and the appearance or layout are important to attract interest. Supporting elements such as short and long videos and expert opinions are needed by students. Laboratory facilities and art spaces are representative places to apply more contextual learning. This research is prepared for the need of development and for other researchers who need analysis and framework of teaching materials from the book elements, learning outcomes, and supporting components.